Effects of dietary postbiotic and inulin on growth performance, IGF1 and GHR mRNA expression, faecal microbiota and volatile fatty acids in broilers - Kareem, Karwan Yaseen (BMC Vet Res, 2016)
BACKGROUND: Postbiotics (metabolic products by lactic acid bacteria) and prebiotics have been established as substitute to antibiotics in order to enhance immunity and growth performance in broiler chickens. Nonetheless, insufficient information is available on the effects of postbiotics and prebiotics combination on growth performance, faecal microbiota, pH and volatile fatty acids (VFA), as well as liver insulin like growth factor 1 (IGF1) and growth hormone receptor (GHR) mRNA expressions in broiler chickens. The aim of this experiment was to evaluate the effects of different types of postbiotics with different levels of prebiotic (inulin) on broiler for those parameters. RESULTS: The results showed that birds fed T3: (0.3 % RI11 + 0.8 % Inulin), T4: (0.3 % RI11 + 1.0 % Inulin), and T6: (0.3 % RG14+ 1.0 % Inulin) had higher (p < 0.05) final body weight (BW) and total weight gain (WG) than other treatments. Birds fed T3 had lower feed conversion ratio (FCR) which was significantly different from those fed with negative control diet but was similar to other treatments. Postbiotic and inulin increased (p < 0.05) faecal lactic acid bacteria (LAB) and reduced (p < 0.05) Enterobacteriaceae count. Birds fed T4 and T6 had higher faecal acetic acid and propionic acid respectively, and both had higher total VFA and lactic acid bacteria but lower pH and Enterobacteriaceae (ENT) counts compared to other treatments. The liver of birds fed T4 and T6 had higher IGF1 expression compared to other treatments while T6 had higher GHR mRNA expression compared to other treatments. CONCLUSIONS: Results indicate that the addition of postbiotics and inulin combinations had beneficial effects on total BW, feed efficiency, mucosa architecture and IGF1 and GHR mRNA expression in broiler chickens.